Prinsip Good Governance Pada Pengelolaan Lembaga Zakat - Alhalimi, Kamila; J, Julina; H, Herlinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research describes zakat management based on the principles of good governance. This research method uses library research such as secondary data in the form of books, journal articles or other literature based on the topic being discussed. It is necessary for the Zakat Amil Institution (LAZ) to improve its professional performance in order to meet the interests of stakeholders. The application of Good Governance principles in zakat management so that zakat can be managed. maximum and achieve the desired goals